Drupal for Education and Elearning. - Robertson, James Gordon (Packt Publishing, 2013)
With clear instructions and plenty of screenshots, this book provides all the support and guidance you will need as you begin to create your classroom website. Step-by-step tutorials show you how to use Drupal in the most efficient and effective ways possible. People new to Drupal will find a good introduction of the basics; while more experienced users will learn useful tips and tricks for using Drupal in a classroom context. If you are an teacher, tutor or an educator who wants to build a website for your classroom, be it elementary or any higher education, ""Drupal 7 for Education and E-Lear.